Development and validation of an age-sex-ethnicity-specific metabolic syndrome score in the Chinese adults - Yang, Shujuan; Yu, Bin; Yu, Wanqi; Dai, Shaoqing; Feng, Chuanteng; Shao, Ying; Zhao, Xing; Li, Xiaoqing; He, Tianjing; Jia, Peng (Nature communications, 2023)
Metabolic syndrome (MetS) is characterized by metabolic dysfunctions and could predict future risk for cardiovascular diseases (CVDs). However, the traditionally defined dichotomous MetS neither reflected MetS severity nor considered demographic variations. Here we develop a continuous, age-sex-ethnicity-specific MetS score based on continuous measures of the five metabolic dysfunctions (waist circumference [WC], triglycerides [TG], high-density lipoprotein cholesterol [HDL-C], mean arterial pressure [MAP], and fasting blood glucose [FBG]). We find that the weights of metabolic dysfunctions in the score vary across age-sex-ethnicity-specific subgroups, with higher weights for TG, HDL-C, and WC. Each unit increase in the score is associated with increased risks for hyperlipidemia, diabetes, and hypertension, and elevated levels of HbA1c, cholesterol, body mass index, and serum uric acid. The score shows high sensitivity and accuracy for detecting CVD-related risk factors and is validated in different geographical regions. Our study would advance early identification of CVD risks and, more broadly, preventive medicine and sustainable development goals. Metabolic syndrome (MetS) could predict future risk for cardiovascular diseases (CVDs), but the traditionally defined dichotomous MetS cannot reflect MetS severity and demographic variations. Here, the authors develop a continuous, age-sex-ethnicity-specific MetS score to better identify CVD risk in a Chinese population.